Promoting Engaging Interaction by Using Quizizz: An Option to Teach English During Pandemic Covid-19 - Ni Putu Ade Resmayani; Rieka Yulita Widaswara (Linguistics and ELT Journal, 2022)
One of the vital pedagogical elements that will help students master a language is interaction in the classroom. Unfortunately, the conversation quickly changed in a virtual classroom because of the COVID-19 pandemic. Quizizz is well-known for effectively facilitating remote learning as a learning platform that provides various features. This project will use Quizizz as a substitute for traditional lectures for students in non-English departments. The Quizizz platform in this study's descriptive qualitative research approach provides a deep discussion on the use of the Quizizz platform in creating interactive remote lecturing. Quizizz was found highly beneficial and engaging for many students, and they strongly supported utilizing it in other disciplines. It is also important to highlight that the students' improved motivation to learn English was aided by their increased Quizizz engagement. Furthermore, this platform specifically increased student involvement in online English education, notably for students not enrolled in the English Department. Finally, despite the outbreak, providing Quizizz to students positively affected them. Students still find motivation and enthusiasm in virtual interactive learning experiences through Quizizz.